"Failure is just another try": Re-framing failure in school through the FUSE studio approach. (2020) - Hilppö, Jaakko; Stevens, Reed
Highlights: Shows how failure can be framed as productive for learning in schools. Shows two ways in which failure was framed in the FUSE studio. Shows that failure as productive for learning was a significant part of participants experience. Suggests new ways in which learning experiences in school could be arranged to support learning the productivity of failure. Abstract: In an era of high-stakes testing and performance demands that regulate future educational opportunities and affect how schools are managed and funded, failure can easily become stigmatized in the practices of schooling. In turn, it can lead students to avoid activities in which they can be evaluated as failing. As researchers, if we wish to help students recognize the value of failure in the process of learning and to capitalize on failures as significant learning opportunities, we must find ways in which failure at school can be reframed as something productive, rather than punitive. In this study, we investigated how student experience in a FUSE Studio—an alternative infrastructure for learning in schools organized around principles of student choice and interest (Stevens et al., 2016 )— support a different, more productive 'use' of failure. Our study is an investigation of how failure was framed in the FUSE Studio by students and teachers and whether these participants recognized learning from failure as a productive part of their FUSE Studio experience. Our analysis, which was based on a year-long video ethnography conducted in a typical FUSE Studio, revealed two distinct ways in which failure was framed. In addition, an analysis of participant interviews highlighted that the students and a facilitator viewed failure as a significant and productive part of their FUSE Studio experience. In sum, the study contributes to the existing literature on the value of failure for learning, by highlighting a way that failure can be framed as being productive for both students and teachers.